(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Since the end of the Cold War, the U.S. Navy has made profound changes in its strategic concepts, operating structures, naval doctrines and combat systems to adapt its forces both to the changing security environment and to achieving a Revolution in Military Affairs that promised to transform war at sea. This article examines those changes – firstly oriented towards littoral warfare, later to achieve the revolution and nowadays to secure its access to any point of the globe by contributing to the Air-Sea Battle – aimed at maintaining the relevance of the U.S. Navy in American foreign policy